Tube and wing aircraft design analysis: data - Chan, Joseph; Sun, Yicheng; Smith, Howard (Cranfield University, 2024)
This dataset is generated using GENUS for the conference paper "Airliner conceptual designs for the application of alternative fuels" and an upcoming journal paper
Keywords: Aircraft design'; 'GENUS'; 'Sustainability'; 'Emissions'